Endoscopic radiofrequency biliary ablation treatment: A comprehensive review. Issue 3 (4th January 2019) - Larghi, Alberto; Rimbaș, Mihai; Tringali, Andrea; Boškoski, Ivo; Rizzatti, Gianenrico; Costamagna, Guido
Abstract : Radiofrequency ablation (RFA) functions by delivering thermal energy within tissue, the result of a high‐frequency alternating current released from an active electrode, leading to coagulative necrosis and cellular death. Recently, a biliary catheter working on a guidewire has been developed and a number of studies have so far been carried out. The present article provides a comprehensive review of the literature on the results of the use of RFA for the clinical management of patients with unresectable malignant biliary strictures, benign biliary strictures, and residual adenomatous tissue in the bile duct after endoscopic papillectomy. Available data show that biliary RFA treatment is a promising adjuvant therapy in patients with unresectable malignant biliary obstruction. The procedure is safe, well tolerated and improves stent patency and survival, even though more studies are warranted. In patients with residual endobiliary adenomatous tissue after endoscopic papillectomy, a significant rate of neoplasia eradication after a single RFA session has been reported, thus favoring this treatment over surgical intervention. In these patients, as well as in those with benign biliary strictures, dedicated probes with a short electrode able to focus the RF current on the short stenosis are needed to expand RFA treatment for these indications.